2017
DOI: 10.1200/jop.2017.024810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intensity-Modulated Radiotherapy on Health Care Costs of Patients With Anal Squamous Cell Carcinoma

Abstract: Purpose Drivers of variation in the cost of care after chemoradiotherapy for the management of anal squamous cell carcinoma (SCC) have not been fully elucidated. We sought to characterize the direct and indirect impact of radiotherapy modality on health care costs among patients with anal SCC. Patients and Methods A retrospective cohort study was performed using the 2014 linkage of the SEER-Medicare database. We identified 1,025 patients with anal SCC diagnosed between 2001 and 2011 and treated with chemorad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In light of these data together with the aforementioned lack of further prospective work regarding this topic, it is important to appraise the cost-effectiveness of IMRT in this clinical circumstance. Two studies of cost have been performed using the SEER-Medicare database, demonstrating higher base costs for IMRT but decreased hospitalization-related costs (33,34). Presently, however, because neither of these "cost" studies were comparative "cost-effectiveness" studies, this question remains unresolved to date with respect to formal medico-economic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these data together with the aforementioned lack of further prospective work regarding this topic, it is important to appraise the cost-effectiveness of IMRT in this clinical circumstance. Two studies of cost have been performed using the SEER-Medicare database, demonstrating higher base costs for IMRT but decreased hospitalization-related costs (33,34). Presently, however, because neither of these "cost" studies were comparative "cost-effectiveness" studies, this question remains unresolved to date with respect to formal medico-economic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The management of undue side effects was evaluated in a 2014 linked SEER-Medicare database showing unplanned health care utilization costs such as emergency department visits and hospitalizations were higher among patients receiving 3DCRT over IMRT (median, $4,957 vs. $711; P=0.02) however, IMRT was associated with higher total costs than 3DCRT as expected (median total cost $35,890 vs. $27,262; P<0.001) (17). In the present study, income quartile and insurance status were not associated with increased utilization of IMRT, which may indicate high acceptance rates of insurance companies of IMRT.…”
Section: Discussionmentioning
confidence: 88%
“…In another study Lester-Coll et al concluded that the net cost of IMRT was $171,792 net cost of 3DCRT was $163,048 [ 20 ]. Chin et al showed that the median total cost for the IMRT group with $35,890 was higher than the 3D-CRT group with $27,262 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%